2001
DOI: 10.1002/ptr.840
|View full text |Cite
|
Sign up to set email alerts
|

Kava and Valerian in the treatment of stress‐induced insomnia

Abstract: Kava and valerian are herbal remedies, claimed to have anxiolytic and sedative properties respectively, without dependence potential or any appreciable side-effects. In this pilot study, 24 patients suffering from stress-induced insomnia were treated for 6 weeks with kava 120 mg daily. This was followed by 2 weeks off treatment and then, 5 having dropped out, 19 received valerian 600 mg daily for another 6 weeks. Stress was measured in three areas: social, personal and life-events; insomnia in three areas also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 9 publications
(7 reference statements)
0
37
0
1
Order By: Relevance
“…Wheatley (2001) found that 600-mg of valerian before bed for 6 weeks improved stress-induced sleep deficit in adult insomniacs.~* in contrast, 0 t h studies report no improvement of subjective sleep quality.176 248 Objective measures of sleep (Le. EEG and activity recordings) show no effect on total sleep time or number of awakenings aftervaierian treaîment in young volunteers 176. ls4 or elderly poor sleepersla6, despite reporteci increases in slow wave sleep and decreased activity in the last third of an 8- Therefore, insomniacs may not be as healthy as the subjects in this study were, andlor may be more tikely to be taking more concomitant medicatious.…”
Section: Ive -Comparisons Between Treatmentsmentioning
confidence: 99%
“…Wheatley (2001) found that 600-mg of valerian before bed for 6 weeks improved stress-induced sleep deficit in adult insomniacs.~* in contrast, 0 t h studies report no improvement of subjective sleep quality.176 248 Objective measures of sleep (Le. EEG and activity recordings) show no effect on total sleep time or number of awakenings aftervaierian treaîment in young volunteers 176. ls4 or elderly poor sleepersla6, despite reporteci increases in slow wave sleep and decreased activity in the last third of an 8- Therefore, insomniacs may not be as healthy as the subjects in this study were, andlor may be more tikely to be taking more concomitant medicatious.…”
Section: Ive -Comparisons Between Treatmentsmentioning
confidence: 99%
“…Various preparations of kava have been marketed since the 1980s, especially in Europe and North America to manage mild anxiety, tension, and restlessness. Some reports also indicate that kava preparations may have analgesic, spasmolytic, neuroprotective, and antimitotic activities [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being used to treat mild or moderate anxiety, kava preparations are used for insomnia, stress, menopause, and muscle fatigue. Experiments with animal models and epidemiological data have shown that kava has a wide spectrum of therapeutic properties, such as sedative, anxiolytic, analgesic, and neuroprotective effects (Jamieson and Duffield, 1990;Martin et al, 2000;Wheatley, 2001;Singh and Singh, 2002;Cagnacci et al, 2003). It has been postulated that these activities are achieved through multiple mechanisms, such as blockade of voltage-gated sodium channels (Schirrmacher et al, 1999), enhanced interactions between ligand and corresponding receptors (e.g., aminobutyric acid type A receptor) (Davies et al, 1992), modulation on neurotransmitter release (Baum et al, 1998), inhibition of enzyme activity (e.g., cyclooxygenase-2) (Wu et al, 2002), and decrease in cytokine release (e.g., tumor necrosis factor-␣; TNF-␣) (Hashimoto et al, 2003).…”
mentioning
confidence: 99%